Treatment of Wound Healing with Sequential Therapy to Accelerate Recovery and Inhibit Scar Hyperplasia: A Case Report - Li X; He M; He H (Dove Medical Press, 2021)
Xiaoqing Li,1,* Mei He,1,* Hailun He2- 4 1Department of Medical Cosmetology, Chengdu Second People's Hospital, Chengdu, 610011, People's Republic of China; 2Cosmetics Safety and Efficacy Evaluation Centre, Sichuan University West China Hospital, Chengdu, 610041, People's Republic of China; 3Sichuan Engineering Technology Research Centre of Cosmetic, Chengdu, 610041, People's Republic of China; 4Department of Dermatology, Sichuan University West China Hospital, Chengdu, 610041, People's Republic of China*These authors contributed equally to this workCorrespondence: Hailun He Email Hehailun0803@163.comStudy Design/Patients and Methods: A 19-year-old male was reported to have a postoperative facial trauma suture as a result of being involved in a car accident. Red light-emitting diode (LED) therapy (20 min, 96 J/cm2, 633 nm), Botulinum Toxin Type A 36 IU injection, BroadBand Light and Er:YAG laser at various stages of wound healing were applied as the sequential therapy.Results: Since the correction was promptly apparent and acceptable, the treatment proved secure and efficacious for repairing wound healing.Conclusion: Clinically sequential therapy has demonstrated marked improvement in our case. Scar sequential therapy may offer a new strategy for wound healing recovery.Keywords: wound healing, scar, keloid, treatment